Religion, society, and culture in Malik Bennabi's thought - El-Mesawi, Mohamed El-Tahir (Blackwell Publishing Ltd., 2007)
This chapter attempts to provide a condensed account of the philosophical and sociological thought of the twentieth-century eminent Algerian thinker Malik Bennabi (1905–73). It focuses on his views pertaining to religion, society, and culture. The present chapter consists of three main sections that are prefaced with a short biographical sketch outlining the major stages of Bennabi’s life and career. As will become clear in the pages that follow, Bennabi’s works in general and his The Qur’anic Phenomenon in particular stand out as one of the most well-informed intellectual responses to, and engagement with, modern Western philosophical and scientiﬁc thought. A sense of the unity of human history, a critical and profound philosophical bent of mind, and a sharp awareness of the cross-cultural and intellectual currents at work in the West and the Muslim world: these are major traits of his treatment of various theological, moral, social, and cultural issues. These features are consolidated and given full scope by what can be seen as a visionary passion driving toward transcending the prevailing thought categories, not through shallow and haughty ideological attitude, but through a conscious and creative intellectual commitment to analysis and systematic theorizing. This, it seems, is what enabled Bennabi to boldly question some of the fundamental intellectual premises of modern Western culture and civilization and to realize some of their grave epistemological and moral consequences, while at the same time appreciating the achievements and the beneﬁts it has brought to mankind.